Pendayagunaan Tenaga Pelopor MALARIA (PTM) Pada Daerah-Daerah Endemik Malaria di Propinsi Sumatera Barat (Poltekkes Kemenkes Yogyakarta, 2008)
The eradication and controlling activities on malaria mosquitos still only ad-dressing the vectors such as conducting house spraying, larviciding and ento-mologic survey. These efforts are ineffective because of lack of human factor. In sociological intervention, community involvement are needed to voluntarily help the malaria problem. Those people are called Tenaga Pelopor Malaria (TPM). The study was aimed to develop community empowerment model by forming and activating individuals in the community as TPM. The model is ex-pected to be implemented not only in research areas but also in other malaria endemic areas. The study employed quasi experiment with control group pre and post test design. The research took place at Mandeh Village in Pesisir Selatan Regency and Sijantang Village in Sawahlunto City. There were 10 TPM, each of them took care 10 households and conducting eight visitages in once a week frequency. From every visitage, the development of the house-holds were monitored. The study showed that the TPMs have been founded in West Sumatera Province as a model for other areas. In doing their activities, each TPM was equipped with pocket books and booklets as guidance Results of the FGD showed that in general, people were not fully aware about the characteristics of malaria as well as the related controlling methods. It can be concluded that the TPM intervention were significantly effective in increasing people’s knowledge and attitude (p<0.05). However, no significant effect was found for practice aspects (p>0.05). The local Health Agency is advised to follow-up the program by monitoring dan controlling the TPM’s activities. It is suggested as well, that the local government pay attention by giving incentive in order to motivate the TPM to be more active.